Enhancing the interfacial stability of all-solid-state high-energy sodium-ion batteries by coating materials: First principles calculations - Chun, Gin Hyung; GONG, SANG HYUK; Kim, Hyung seok; Shim, Joon Hyung; Yu, Seungho (Elsevier BV, 2023)
All-solid-state batteries are promising next-generation batteries owing to their enhanced safety and high energy density. Recently, all-solid-state sodium-ion batteries have broadly investigated owing to low price and abundance of sodium. Various types of solid electrolytes (SEs) exhibiting high ionic conductivities have been investigated for all-solid-state Na-ion batteries. However, a few studies have been reported for the interfacial stability of sodium SEs against high-energy cathode materials. In this study, we systematically investigated the interfacial stability between ten sodium superionic conductors and 16 high-energy oxide cathode materials. The calculation results indicated that sodium sulfide and selenide SEs generally exhibit chemical incompatibility with cathode materials, suggesting that interfacial coating should be employed to alleviate the interfacial reaction. We utilized high-throughput screening process to identify promising coating materials between sodium SEs and cathode materials. Eight compounds from 7,398Na-containing compounds were screened as promising coating materials, which considerably reduced the chemical reactivity at the interface. The findings of this study can provide design strategies for the all-solid-state sodium-ion batteries.